1997
DOI: 10.1523/jneurosci.17-16-06226.1997
|View full text |Cite
|
Sign up to set email alerts
|

Differential Localization of Voltage-Dependent Calcium Channel α1Subunits at the Human and Rat Neuromuscular Junction

Abstract: Neurotransmitter release is regulated by voltage-dependent calcium channels (VDCCs) at synapses throughout the nervous system. At the neuromuscular junction (NMJ) electrophysiological and pharmacological studies have identified a major role for P-and/or Q-type VDCCs in controlling acetylcholine release from the nerve terminal. Additional studies have suggested that N-type channels may be involved in neuromuscular transmission. VDCCs consist of pore-forming ␣ 1 and regulatory ␤ subunits. In this report, using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 52 publications
3
53
2
Order By: Relevance
“…The distribution and juxtaposition of the two stains is consistent with results described by Day et al (1997). However, this pattern of distribution was not observed in the tg preparations.…”
Section: N-and R-type Ca 2؉ Channels At Nmj In Tottering Micesupporting
confidence: 90%
“…The distribution and juxtaposition of the two stains is consistent with results described by Day et al (1997). However, this pattern of distribution was not observed in the tg preparations.…”
Section: N-and R-type Ca 2؉ Channels At Nmj In Tottering Micesupporting
confidence: 90%
“…Strikingly, these results suggested that ALS-IgG did not interact with Ca v 2.2 channels, in agreement with previous immunoprecipitation and ELISA results (Arsac et al, 1996). Furthermore, Ca v 2.2 channels remain in denervated muscles (Day et al, 1997;Pagani et al, 2004), whereas ALS-IgG molecular target disappears completely after denervation (Fig. 4).…”
supporting
confidence: 91%
“…Passive transfer of LEMS IgG to mice has been shown to cause a reduction in the quantal release of acetylcholine at the neuromuscular junction, a process that is believed to be mediated by the P͞Q-type VDCC (19,23,24). In addition, recent studies have demonstrated presynaptic expression of the ␣ 1A subunit at the human neuromuscular junction (25). Taken in conjunction with these published studies, our data provide strong evidence that antibodies directed against P͞Q-type VDCCs are responsible for the impairment of neuromuscular transmission in LEMS.…”
Section: Discussionmentioning
confidence: 99%